PENGGUNAAN YAKUWARIGO SAMURAI OLEH TOKOH KIN'EMON DALAM MANGA ONE PIECE ARC WANO KUNI - Tasya Khairunnisa; Maulluddul Haq (Universitas Negeri Padang, 2025)
The use of language by specific characters in literary works is further explored in a linguistic framework known as role language (yakuwarigo). Yakuwarigo refers to a set of spoken language features that can be psychologically associated with particular character types, including traits related to age, gender, occupation, social status, appearance, and personality (Kinsui & Yamakido, 2015). One distinctive type of yakuwarigo in Japanese narratives is samurai role language, also referred to as bushi kotoba. This study aims to analyze the meaning and usage of yakuwarigo bushi kotoba as used by the character Kin'emon in the manga One Piece, applying the theoretical framework of Kinsui (2014). The research employs a qualitative descriptive method, with data collection techniques including observation and note-taking. The findings reveal 10 types of yakuwarigo bushi kotoba. Among these, the most frequently used type by Kin'emon is nu, with 40 occurrences, while the least frequently used are mairu and oo, each with 2 occurrences.